Debating the end of history : the marketplace, utopia, and the fragmentation of intellectual life - Noble, David W. (Critical American studies series., 2012)
Why do modern people assume that there will be perpetual economic growth? Because, David W. Noble tells us in this provocative study of cultural criticism, such a utopian conviction is the necessary foundation for bourgeois culture. One can imagine the existence of modern middle classes only as long as the capitalist marketplace is expanding. For Noble, the related-and relevant-question is, how can the middle classes believe that a finite earth is an environment in which infinite growth is possible? The answer, which Noble so painstakingly charts, is nothing less than a genealogy of th.